Retrospective assessment of the reporting of adverse drug reactions in a Malaysian clinical training center: A short communication - Elkalmi, Ramadan; Elnaem, Mohamed Hassan Abdelaziz; Sabar, Nurmisaliza; Blebil, Ali (Medknow Publications, 2021)
Objectives: This study aimed to assess the completeness and quality of adverse drug reaction (ADR) reports that were submitted to the Pharmacovigilance Unit (PVU) in clinical training center (CTC), Faculty of Medicine, UiTM Sungai Buloh Campus. Materials and Methods: A retrospective study was conducted using all ADR reports that were submitted to the PVU in CTC from December 31, 2000, to December 31, 2018. The completeness was assessed by reviewing all the required elements to be filled in the ADR reports. The quality was assessed by investigating the required information in the ADR reporting form. Descriptive statistics have been used to present the findings. Key Findings: In a total of 31 reports that were submitted to the PVU in CTC, 98.9% of patient's information and 100% of ADR descriptions were completed. Suspected drug information and the reporter's details were completed by 52.2% and 79.6%, respectively. Of 58.0% of the information about seriousness recorded, 38.9% (n = 7) is mild, 44.4% (n = 8) is moderate, and 16.7% (n = 3) is severe. Among all the suspected medicines, drug class of antibiotics (32.4%, n = 12) is the most reported suspected drugs that caused ADR, followed by opioid analgesic (8.1%, n = 3) and nonsteroidal anti-inflammatory drugs (8.1%, n = 3). Conclusion: Further efforts and relevant interventions should be considered to increase the reporting frequency and to enhance the completeness and the quality of the ADR reports in the study setting.